Risk perception and knowledge of protective measures for flood risk planning. The case study of Brindisi (Puglia region) - Santoro, S; Totaro, V; Lovreglio, R; Camarda, D; Iacobellis, V; Fratino, U (Massey University, 2022)
Floods are among the most frequent natural hazards, and flood risk management is a paramount task when planning solutions to reduce their impact on communities. In the last decades, policy makers' actions for flood risk management have been redirected from purely physical self-protective measures towards integrated management strategies by including social components. Assessing flood risk perception and the level of knowledge of citizens regarding protective measures is becoming a pillar for generating innovative flood integrated management strategies. This study aims to highlight multiple aspects which can influence flood risk management in urban areas, providing a preliminary assessment of citizens’ flood risk perception and knowledge of protective measures. Proposed methodology is based on E-survey in order to gather data and Mann-Whitney and Kruskal-Wallis tests to analyze them and has been applied to the case study of Brindisi (Puglia region, Southern Italy). The results suggest that flood risk perception depends on intrinsic components of individuals, mainly related to trust in public strategies and risk communication. It depends on hazard proximity but is uniformly distributed over the whole city, demonstrating that the perception of flood risk can not be related only to river floods. Knowledge of protective measures appears uniformly low by category of citizens and territorial area, particularly for teenagers. The methodological approach has allowed to bring out how the different nature of floods could produce a spatial and social heterogeneity in citizens’ flood risk perception and knowledge of protective measures, revealing latent risk features useful for supporting flood risk planning.
Keywords: 09 Engineering; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences